1993
DOI: 10.1017/s0022112093002265
|View full text |Cite
|
Sign up to set email alerts
|

The role of acoustics in flame/vortex interactions

Abstract: The role of acoustics in flame/vortex interactions is examined via asymptotic analysis and numerical simulation. The model consists of a one-step, irreversible Arrhenius reaction between initially unmixed species occupying adjacent half-planes which are allowed to mix and react by convection and diffusion in the presence of an acoustic field or a time-varying pressure field of small amplitude. The main emphasis is on the influence of the acoustics on the ignition time and flame structure as a function of vorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This is a direct indication of the increased turbulence and entraining effects by acoustics as attributed to the torroidal vortices (Vermeulen and Ramesh, 1998) and the decrease in mixing timescales relative to the flow timescales. Such a result agrees with the numerical results of Jackson et al (1993), who found that flame ignition is always enhanced at high frequencies. It also matches the results of Vermeulen and Yu (1987), who found the strength of the induced vortices approximately increases with frequency.…”
Section: Effect Of Strouhal Numbersupporting
confidence: 92%
“…This is a direct indication of the increased turbulence and entraining effects by acoustics as attributed to the torroidal vortices (Vermeulen and Ramesh, 1998) and the decrease in mixing timescales relative to the flow timescales. Such a result agrees with the numerical results of Jackson et al (1993), who found that flame ignition is always enhanced at high frequencies. It also matches the results of Vermeulen and Yu (1987), who found the strength of the induced vortices approximately increases with frequency.…”
Section: Effect Of Strouhal Numbersupporting
confidence: 92%
“…The vorticity field generated by a single planar pressure wave moving through a cylindrical laminar flame was also examined in [74]. The shock-flame interaction creates vortices, and there has been significant work in flame-vortex-acoustic interactions (for a review, see [75]; for more recent work, see, for example, [76]). …”
Section: Theoretical and Numerical Studiesmentioning
confidence: 99%